أثر الهيكل التّمويلي على الأداء المالي للشّركات المُدرجة في سوق دمشق للأوراق المالية للفترة (2007-2016) - عمار قصي (Latakia University Journal - Economic and Legal Sciences Series, 2018)
This study aims at testing the impact of financing structure (financial leverage) on the performance of listed companies in Damascus Security Exchange, according to accounting performance measures namely: Earning Per Share (EPS); Dividends Per Share (DPS); Stock book Value (BV); Stock Market Value (MV); Return on Assets (ROA); and Return on Equity (ROE). By focusing on two time series: the first series before the current crisis (2007-2011); and the second series during the crisis (2012-2016). In order to analyze and test the hypothesis, the researcher used two models: the static model (Panel data analysis); and the dynamic model (Distributed lag model). The results show that the financing structure (debt ratio) has a positive and significant impact on the return on assets; and the return on equity, and this impact extends for several years later. Finally, no evidence has been provided by the study about the impact of the financing structure on earnings per share; dividends per share; book value per share; and market value per share, as measures of financial performance of the Syrian listed firms. يتناول هذا البحث أثر قرار الهيكل التّمويلي في الشّركات المُساهمة العامة على أداء وعوائد هذه الشّركات، من خلال دراسة حالة الشّركات المُدرجة في سوق دمشق للأوراق المالية، وذلك بالتّركيز على سلسلتين زمنيتين: السّلسلة الأولى قبل الأزمة الراهنة (2007-2011)؛ والثانية خلال الأزمة (2012-2016). ويتمثل الهدف الرئيس لهذا البحث في دراسة العلاقة بين مديونية الشّركة (الرفع المالي) وأثرها على ستة من المؤشرات المالية التقليدية المُستخدمة في قياس الأداء المالي، وهي: العائد على السهم العادي الواحد؛ ونصيب السهم العادي الواحد من الأرباح الموزعة؛ والقيمة الدفترية للسهم؛ والقيمة السوقية للسهم؛ والعائد على الاستثمار؛ والعائد على حق الملكية. ولتحقيق هدا الهدف، اعتمد الباحث على المدخل الاستنباطي لصياغة فرضيات البحث، ومن أجل اختبار هذه الفرضيات اعتمد الباحث على تحليل الانحدار الخطي البسيط باستخدام نموذجين: نموذج السّلسلة الزمنية المقطعية؛ ونموذج التباطؤ الزمني. توصلت الدّراسة إلى وجود أثر إيجابي للهيكل التّمويلي (نسبة المديونية) على مقاييس الأداء الأتية: معدل العائد على الاستثمار؛ ومعدل العائد على حقوق الملكية، وأن هذا الأثر يمتد لعدة سنوات لاحقة. في حين لم تُقدم نتائج الدّراسة أية أدلة على وجود أثر للهيكل التّمويلي على عائد السهم الواحد؛ وتوزيعات السهم الواحد؛ والقيمة الدفترية للسهم؛ والقيمة السوقية للسهم، كمقاييس للأداء المالي للشّركات محل الدّراسة.